THE ANTI-INFLAMMATORY EFFECT'S PHYSICAL EXERCISE IN THE PREVENTION OF CHRONIC NONCOMMUNICABLE DISEASES (Fiep Bulletin - online, 2013)
The NCDs are the leading cause of death worldwide, and are associated with functional disabilities. The main installation mechanisms of NCDs are chronic subclinical inflammation, insulin resistance and MS. All these mechanisms are associated with the presence of proinflammatory substances in the body. From these data it was observed that the EF appears in a prominent position in the prevention of these diseases, because it alters the body composition and physiological markers such as heart rate and blood pressure, also acts as anti-inflammatory agent. Thus the work has as main objective to analyze the mechanisms of prophylactic EF regarding installation of NCDs, as well as specific goal: Aim kinds of effective exercises for an anti-inflammatory action, with respect to NCDs. Therefore, we performed a systematic literature review conducted in electronic databases, books and articles, using the area as important authors Pedersen, Jose Maria Santarém, Neil Walsh, Petersen, Carnevali Jr. has been observed so exercises more intense and of limited duration, such as TF, are safer to prevent DCNT, and must be used as a central part of a program for training, aerobic exercises while low intensity can be used in regenerative periods provided they are controlled.
Keywords: Exercise; Inflammation; NCD